2011
DOI: 10.1016/j.nuclphysa.2011.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Study of 9Be+12C elastic scattering at energies near the Coulomb barrier

Abstract: In this work, angular distribution measurements for the elastic channel were performed for the 9Be+12C reaction at the energies ELab=13.0, 14.5, 17.3, 19.0 and 21.0 MeV, near the Coulomb barrier. The data have been analyzed in the framework of the double folding S\~ao Paulo potential. The experimental elastic scattering angular distributions were well described by the optical potential at forward angles for all measured energies. However, for the three highest energies, an enhancement was observed for intermed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For 9 Be the situation is even less clear than for 7 Li, since in some cases the real and imaginary potentials which fit the elastic scattering data do not obey the dispersion relation [121,122,60]. For this projectile there are not too many systems investigated: 12 209 Bi [122].…”
Section: Threshold Anomaliesmentioning
confidence: 95%
“…For 9 Be the situation is even less clear than for 7 Li, since in some cases the real and imaginary potentials which fit the elastic scattering data do not obey the dispersion relation [121,122,60]. For this projectile there are not too many systems investigated: 12 209 Bi [122].…”
Section: Threshold Anomaliesmentioning
confidence: 95%
“…The energy dependence of the nuclear OP at the Coulomb barrier is investigated to examine the impact of breakup, transfer, and other processes on the elastic channels for reactions with low breakup threshold energies. Several recent works [5,10,[50][51][52][53][54][55][56][57][58] have investigated the energy dependence of the OP in the elastic scattering of WB stable, radioactive, and halo nuclei on a variety of targets. Figure 7 (left panel) depicts the energy dependence of the resulting real and imaginary volume integrals for 7 Be+ 28 Si OPs, as tabulated in table 1.…”
Section: Threshold Behaviormentioning
confidence: 99%
“…The BTA analysis has been reported by studying the energy dependence of the optical potential that accounts for the reactions of systems involving stable weakly bound projectiles like 6 Li [8,[12][13][14][15][16][17][18][19][20][21][22][23][24], 7 Li [8,13,15,19,21,22,24,[24][25][26][27], and 9 Be [3,[28][29][30][31][32], as well as radioactive like 6 He [33,34], 7 Be and 8 B [35]. In all these studies, it was found that the imaginary part of the optical potential does not drop to zero at energies centered on the Coulomb barrier, as expected when the usual TA is observed.…”
Section: Introductionmentioning
confidence: 99%